A novel λ integrase-mediated seamless vector transgenesis platform for therapeutic protein expression - Makhija, Harshyaa (2019)
Advances in stem cell engineering, gene therapy and molecular medicine often involve genome engineering at a cellular level. However, functionally large or multi transgene cassette insertion into the human genome still remains a challenge. Current practices such as random transgene integration or targeted endonuclease-based genome editing are suboptimal and might pose safety concerns. Taking this into consideration, we previously developed a transgenesis tool derived from phage λ integrase (Int) that precisely recombines large plasmid DNA into an endogenous sequence found in human Long INterspersed Elements-1 (LINE-1). Despite this advancement, biosafety concerns associated with bacterial components of plasmids, enhanced uptake and efficient transgene expression remained problematic. We therefore further improved and herein report a more superior Int-based transgenesis tool. This novel Int platform allows efficient and easy derivation of sufficient amounts of seamless supercoiled transgene vectors from conventional plasmids via intramolecular recombination as well as subsequent intermolecular site-specific genome integration into LINE-1. Furthermore, we identified certain LINE-1 as preferred insertion sites for Int-mediated seamless vector transgenesis, and showed that targeted anti-CD19 chimeric antigen receptor gene integration achieves high-level sustained transgene expression in human embryonic stem cell clones for potential downstream therapeutic applications.